Trabecular architecture in the thumb of Pan and Homo: implications for investigating hand use, loading, and hand preference in the fossil record. Issue 4 (8th August 2016) - Stephens, Nicholas B.; Kivell, Tracy L.; Gross, Thomas; Pahr, Dieter H.; Lazenby, Richard A.; Hublin, Jean‐Jacques; Hershkovitz, Israel; Skinner, Matthew M.
Abstract: Objectives: Humans display an 85–95% cross‐cultural right‐hand bias in skilled tasks, which is considered a derived behavior because such a high frequency is not reported in wild non‐human primates. Handedness is generally considered to be an evolutionary byproduct of selection for manual dexterity and augmented visuo‐cognitive capabilities within the context of complex stone tool manufacture/use. Testing this hypothesis requires an understanding of when appreciable levels of right dominant behavior entered the fossil record. Because bone remodels in vivo, skeletal asymmetries are thought to reflect greater mechanical loading on the dominant side, but incomplete preservation of external morphology and ambiguities about past loading environments complicate interpretations. We test if internal trabecular bone is capable of providing additional information by analyzing the thumb of Homo sapiens and Pan . Materials and methods: We assess trabecular structure at the distal head and proximal base of paired (left/right) first metacarpals using micro‐CT scans of Homo sapiens ( n  = 14) and Pan ( n  = 9). Throughout each epiphysis we quantify average and local bone volume fraction (BV/TV), degree of anisotropy (DA), and elastic modulus ( E ) to address bone volume patterning and directional asymmetry. Results: We find a right directional asymmetry in H. sapiens consistent with population‐level handedness, but also report a left directional asymmetry in Pan that may be the result of postural and/or locomotor loading. Conclusion: We conclude that trabecular bone is capable of detecting right/left directional asymmetry, but suggest coupling studies of internal structure with analyses of other skeletal elements and cortical bone prior to applications in the fossil record.